Outcome Predictors of Biopsy-Proven Myeloperoxidase-Anti-Neutrophil Cytoplasmic Antibody-Associated Glomerulonephritis - Ge, Yifei; Yang, Guang; Yu, Xiangbao; Sun, Bin; Zhang, Bo; Yuan, Yanggang; Zeng, Ming; Wang, Ningning; Mao, Huijuan; Xing, Changying (Frontiers in Immunology, 2021)
Objective: To determine the prognostic values of histopathologic classification of myeloperoxidase-anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis and other clinical and laboratory features at the time of presentation on renal and patient survival associated with myeloperoxidase-ANCA-associated glomerulonephritis (MPO-ANCA-GN). Methods: A total of 112 patients diagnosed with MPO-ANCA-GN from October 2005 to December 2018 were enrolled. The baseline clinical characteristics, renal histopathological data, and risk factors predictive of renal and patient survival were retrospectively analyzed. Results: All 112 patients underwent renal biopsy. Disease in 32 patients was classified as focal, 26 as mixed, 29 as crescentic, and 25 as sclerotic. Over a median follow-up period of 41.5 months, there were 44 patients dialysis-dependent. The renal survival rate was significantly higher in the focal group than the other groups (p <0.001) and significantly lower in the sclerotic group (p <0.05). In addition, disease histopathologically classified as sclerotic (p =0.044), high serum creatinine level (≥320 μmol/L, p <0.001), low albumin (< 30 g/L, p =0.024) and hemoglobin level (<90 g/L, p =0.044) were associated with a greater risk of ESRD. After follow-up, 70 (62.5%) of 112 patients survived. Old age (≥60 years, p =0.018) and low serum albumin (<30 g/L, p =0.006) were significant risk factors for patient survival. Conclusion: Among patients with MPO-ANCA-GN, those with poor renal function, disease histopathologically classified as sclerotic, and lower albumin and hemoglobin levels were risk factors for ESRD, while older age and low serum albumin level were associated with a greater risk for all-cause mortality.